Adaptation and validation of the Berlin questionnaire of competence in evidence-based dentistry for dental students: a pilot study - Imorde, Laura; Möltner, Andreas; Runschke, Maren; Weberschock, Tobias Bernd; Rüttermann, Stefan; Gerhardt-Szép, Susanne (BMC medical education, 2020)
The purpose of this pilot study was to create a valid and reliable set of assessment questions for examining Evidence-based Dentistry (EbD) knowledge. For this reason, we adapted and validated for dental students the Berlin Questionnaire (BQ), which assesses Evidence-based Medicine (EbM) abilities.
Gesehen am 08.06.2020